1995
DOI: 10.1111/j.1440-1630.1995.tb01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Employment trends for occupational therapists: An analysis of employment advertisements in the Sydney Morning Herald 1984–90

Abstract: Despite rapid growth in the number of occupational therapy graduates in Australia, almost no data are available concerning the demand and the expectations of employers. This study surveyed 6298 advertised positions available to occupational therapists, social workers, psychologists and counsellors in the state of New South Wales during the years 1984–90. Over this period the demand for occupational therapists grew by 53%, which exceeded the growth in demand for social workers and psychologists, but was less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A study completed on the first cohort of graduates (2005) from the same occupational therapy course found that 44.4% of respondents were employed in hospitals (Doherty, Stagnitti & Schoo, ). An earlier study of advertised jobs in Sydney from 1984 to 1990 showed most common employment advertised was within hospitals, 48.6%, followed by community health 29.5%, private 7.8% and welfare 7.1% (Franklin et al ., ). A more recent study in Queensland identified the number of advertisements for occupational therapy roles as being 42% in public health, 33.4% in private companies, 11.1% not for profit organisations and 6.7% in public non‐health settings (Broome & Gillen, ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A study completed on the first cohort of graduates (2005) from the same occupational therapy course found that 44.4% of respondents were employed in hospitals (Doherty, Stagnitti & Schoo, ). An earlier study of advertised jobs in Sydney from 1984 to 1990 showed most common employment advertised was within hospitals, 48.6%, followed by community health 29.5%, private 7.8% and welfare 7.1% (Franklin et al ., ). A more recent study in Queensland identified the number of advertisements for occupational therapy roles as being 42% in public health, 33.4% in private companies, 11.1% not for profit organisations and 6.7% in public non‐health settings (Broome & Gillen, ).…”
Section: Discussionmentioning
confidence: 97%
“…Language used to describe employment also varies significantly between data collection methods and studies which report on employment. The studies cited in this paper use varied terminology to describe what is essentially the same aspect of employment (Broome & Gillen, ; Doherty et al ., ; Franklin et al ., ). Examples of such terminology include principal role, setting, scope of practice and employment type, with varied understanding of what each of these are and then the subcategories within.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While occupational therapy employment has always been fairly broad (Franklin et al 1995), these high-demand areas may represent shifts in the profession from hospital work into primarily community-based work. This is a departure from the dominant discourse in more traditional occupational therapy texts, which focus on hospital-based skills and cases.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational therapists and graduates should not necessarily expect to work under the title of 'occupational therapist', but may be employed in, for example, an interdisciplinary role, perhaps as an occupational rehabilitation consultant, manager, assessor, academic, researcher, professional development officer, hand therapist, or sales executive. There is also an increasing privatization of occupational therapy jobs, with 34.6% of job advertisements coming from the private sector (as compared with 8% in the 1980s; Franklin et al 1995). Non-traditional practice placements, of the type currently included in many accredited undergraduate occupational therapy programmes, may help students to understand and explore a variety of models of service provision.…”
Section: Discussionmentioning
confidence: 99%